Experimental and Theoretical Study on the Cycloreversion of a Nucleobase‐Derived Azetidine by Photoinduced Electron Transfer. Issue 57 (11th September 2018) - Fraga‐Timiraos, Ana B.; Francés‐Monerris, Antonio; Rodríguez‐Muñiz, Gemma M.; Navarrete‐Miguel, Miriam; Miranda, Miguel A.; Roca‐Sanjuán, Daniel; Lhiaubet‐Vallet, Virginie
Abstract: Azetidines are interesting compounds in medicine and chemistry as bioactive scaffolds and synthetic intermediates. However, photochemical processes involved in the generation and fate of azetidine‐derived radical ions have scarcely been reported. In this context, the photoreduction of this four‐membered heterocycle might be relevant in connection with the DNA (6‐4) photoproduct obtained from photolyase. Herein, a stable azabipyrimidinic azetidine (AZTm ), obtained from cycloaddition between thymine and 6‐azauracil units, is considered to be an interesting model of the proposed azetidine‐like intermediate. Hence, its photoreduction and photo‐oxidation are thoroughly investigated through a multifaceted approach, including spectroscopic, analytical, and electrochemical studies, complemented by CASPT2 and DFT calculations. Both injection and removal of an electron result in the formation of radical ions, which evolve towards repaired thymine and azauracil units. Whereas photoreduction energetics are similar to those of the cyclobutane thymine dimers, photo‐oxidation is clearly more favorable in the azetidine. Ring opening occurs with relatively low activation barriers (<13 kcal mol −1 ) and the process is clearly exergonic for photoreduction. In general, a good correlation has been observed between the experimental results and theoretical calculations, which has allowed a synergic understanding of the phenomenon. Abstract : Radical reversion : The ring‐opening reaction of an azetidine derivative has been studied in detail by using experimental and computational methodologies. Both photoinduced electron injection and abstraction lead to the cycloreversion of the heterocycle (see figure).